Comparison of (11)C-4′-thiothymidine, (11)C-methionine, and (18)F-FDG PET/CT for the detection of active lesions of multiple myeloma - Okasaki, Momoko (Ann Nucl Med, 2014)
PURPOSE: The aims of this study were to evaluate the possibility of using (11)C-methionine ((11)C-MET) and (11)C-4′-thiothymidine ((11)C-4DST) whole-body PET/CT for the imaging of amino acid metabolism and DNA synthesis, respectively, when searching for bone marrow involvement in patients with multiple myeloma (MM) and to compare these findings with those for (18)F-FDG PET/CT and aspiration cytology. METHODS: A total of 64 patients with MM, solitary plasmacytoma, monoclonal gammopathy of undetermined significance, or an unspecified diagnosis were prospectively enrolled. All the patients underwent three whole-body PET/CT examinations within a period of 1 week. First, the tracer accumulation was visually evaluated as positive, equivocal, or negative for 55 focal lytic lesions visualized using CT in 24 patients. Second, the percentages of marrow plasma cells as calculated using a bone marrow aspiration smear and tracer accumulation were evaluated in the posterior iliac crests of 36 patients. RESULTS: Among the 55 lytic lesions, the (11)C-MET and (11)C-4DST findings tended to reveal more positive findings than the (18)F-FDG findings. Based on the standard criteria for the diagnosis of active myeloma using the percentage of marrow plasma cells, significant differences were found between the (18)F-FDG and (11)C-MET findings and between the (18)F-FDG and (11)C-4DST findings, but no significant difference was observed between the (11)C-MET and (11)C-4DST findings. CONCLUSION: The addition of (11)C-MET and (11)C-4DST to (18)F-FDG when performing PET/CT enabled clearer evaluations of equivocal lesions. Based on cytological diagnostic criteria, (11)C-MET and (11)C-4DST were more sensitive than (18)F-FDG for the detection of active lesions. (11)C-MET and (11)C-4DST were more useful than (18)F-FDG for the detection of active lesions, especially during the early stage of disease.